An engineered promoter driving expression of a microbial avirulence gene confers recognition of TAL effectors and reduces growth of diverse Xanthomonas strains in citrus. (7th September 2016) - Shantharaj, Deepak; Römer, Patrick; Figueiredo, Jose F. L.; Minsavage, Gerald V.; Krönauer, Christina; Stall, Robert E.; Moore, Gloria A.; Fisher, Latanya C.; Hu, Yang; Horvath, Diana M.; Lahaye, Thomas; Jones, Jeffrey B.
Summary: Xanthomonas citri ssp. citri ( X. citri ), causal agent of citrus canker, uses transcription activator‐like effectors (TALEs) as major pathogenicity factors. TALEs, which are delivered into plant cells through the type III secretion system (T3SS), interact with effector binding elements ( EBE s) in host genomes to activate the expression of downstream susceptibility genes to promote disease. Predictably, TALEs bind EBE s in host promoters via known combinations of TALE amino acids to DNA bases, known as the TALE code. We introduced 14 EBE s, matching distinct X. citri TALEs, into the promoter of the pepper Bs3 gene ( ProBs31EBE ), and fused this engineered promoter with multiple EBE s ( ProBs314EBE ) to either the β‐glucuronidase ( GUS ) reporter gene or the coding sequence (cds) of the pepper gene, Bs3 . TALE‐induced expression of the Bs3 cds in citrus leaves resulted in no visible hypersensitive response (HR). Therefore, we utilized a different approach in which ProBs31EBE and ProBs314EBE were fused to the Xanthomonas gene, avrGf1, which encodes a bacterial effector that elicits an HR in grapefruit and sweet orange. We demonstrated, in transient assays, that activation of ProBs314EBE by X. citri TALEs is T3SS dependent, and that the expression of AvrGf1 triggers HR and correlates with reduced bacterial growth. We further demonstrated that all tested virulent X. citri strains from diverse geographical locations activate ProBs314EBE . TALEs are essential for the virulence of X. citri strains and, because the engineered promoter traps are activated by multiple TALEs, this concept has the potential to confer broad‐spectrum, durable resistance to citrus canker in stably transformed plants.